2006
DOI: 10.1183/09031936.06.00143704
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of anaemia of chronic disease in COPD

Abstract: Anaemia of chronic disease (ACD), with chronically low levels of circulating haemoglobin, is an immune driven abnormality that occurs in many inflammatory diseases, and also in chronic heart failure. Although chronic obstructive pulmonary disease (COPD) is ''traditionally'' associated with polycythaemia, the systemic inflammation that is now recognised as a feature of COPD makes it a possible cause of ACD. If present in COPD, anaemia could worsen dyspnoea and limit exercise tolerance.Preliminary evidence sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
2
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 54 publications
7
114
2
23
Order By: Relevance
“…Portillo et al (38) suggested that the rate of anemia is likely elevated in severe COPD when comparison was done between them and general COPD patients. In discordance to our result, Similowski et al (30) suggested that anemia in COPD patients may be more common than expected, presents in 10-15% of COPD patients who have severe forms of the disease. And Casanova et al (39) found that patients who had anemia tend to have more severe form of COPD in terms of FEV1, with a prevalence of anemia in cases with very severe COPD near 9%.…”
Section: ) Electrocardiogram (Ecgcontrasting
confidence: 56%
“…Portillo et al (38) suggested that the rate of anemia is likely elevated in severe COPD when comparison was done between them and general COPD patients. In discordance to our result, Similowski et al (30) suggested that anemia in COPD patients may be more common than expected, presents in 10-15% of COPD patients who have severe forms of the disease. And Casanova et al (39) found that patients who had anemia tend to have more severe form of COPD in terms of FEV1, with a prevalence of anemia in cases with very severe COPD near 9%.…”
Section: ) Electrocardiogram (Ecgcontrasting
confidence: 56%
“…If the patient was known to suffer from diabetes, chronic lung disease, or heart failure, and no other underlying cause of ACD could be established, these diseases were assigned as the underlying cause of ACD. [7][8][9][10][11][12][13] Any prescription of oral iron supplementation, as well as the time (in weeks) from the confirmation of ACD to the establishment of the underlying cause were also recorded.…”
Section: Data Collectionmentioning
confidence: 99%
“…[3][4][5][6] This type of anaemia can be caused by a variety of conditions, including acute and chronic infections, chronic diseases, autoimmune disorders, acute trauma, surgical interventions, renal failure, heart failure, and malignancies. [7][8][9][10][11][12][13] ACD is described as a functional iron deficiency caused by elevated hepcidin levels, which implies that oral iron supplementation is unnecessary. [14][15][16] Patients with ACD aged 50 years have a relative risk for mortality of 1.48 compared to adults without anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is observed in 10 -15% of patients with COPD (ref. 34 ). Anemic COPD patients have a higher risk of death, morbidities, and hospital admission in comparison to non-anemic COPD patients [34][35][36] .…”
Section: Components Of Copd Prognostic Scorementioning
confidence: 99%
“…New findings from a variety of published studies were incorporated during the development of the COPD prognostic score . Hemoglobin levels were also regarded as a candidate component as studies have reported hemoglobin levels have considerable impact on the mortality of COPD patients [34][35][36][37] . In a conscious effort to simplify the use of this prognostic score, factors needing specialized facilities such as exercise tolerance tests or tests that are not easily duplicated, were excluded.…”
Section: Development Of the Copd Prognostic Scorementioning
confidence: 99%